Special Issue on Advanced Sensing and Control Technologies in Power Electronics - Bernacki, Krzysztof; Novak, Mateja (Sensors (Basel, Switzerland), 2025)
Power electronics performs a key role in today’s energy systems, and its development is increasingly combined with advanced sensor-critical techniques and novel control algorithms that significantly enhance system adaptability, reliability, and robustness against disturbances and cyber threats [...]